2020
DOI: 10.1167/iovs.61.6.36
|View full text |Cite
|
Sign up to set email alerts
|

Lamina Cribrosa Moves Anteriorly After Trabeculectomy in Myopic Eyes

Abstract: The purpose of this study was to investigate changes in lamina cribrosa (LC) depth after trabeculectomy in myopic eyes using enhanced depth imaging (EDI) spectraldomain optical coherence tomography (SD-OCT). METHODS. Serial horizontal B-scans of the optic nerve head of 41 myopic eyes with primary open-angle glaucoma (POAG) were obtained before and 3 months after trabeculectomy using EDI SD-OCT. LC depth, defined as the distance from the opening plane of Bruch's membrane to the level of the anterior LC surface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Subsequently, through cross-sectional ONH analysis using SD-OCT, it was found that the depth of the LC decreased and its thickness increased [8]. Changes in the LC depth after the IOP reduction via glaucoma filtration surgery were also reported to be observed in myopic eyes with a tilted disc [16]. It was also reported that the LC curvature flattened and the LC depth decreased as the IOP decreased after surgery [17,18].…”
Section: Discussionmentioning
confidence: 94%
“…Subsequently, through cross-sectional ONH analysis using SD-OCT, it was found that the depth of the LC decreased and its thickness increased [8]. Changes in the LC depth after the IOP reduction via glaucoma filtration surgery were also reported to be observed in myopic eyes with a tilted disc [16]. It was also reported that the LC curvature flattened and the LC depth decreased as the IOP decreased after surgery [17,18].…”
Section: Discussionmentioning
confidence: 94%
“…DVC estimates of LC strain along with shifts in LC surface position have been estimated following acute changes in IOP after suture lysis posttrabeculectomy 45 and with ophthalmodynamometric compression (ODM). 4 9 Short-term responses have also been evaluated following surgical 46 or medical IOP lowering, 47 , 48 but these changes may incorporate more chronic remodeling responses as well. ODM measurements of IOP elevation in human subjects are the most similar to the current study, which focuses on changes in LC surface position following manometric IOP elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) has emerged over the last decade as the most widely used tool to image the ONH in vivo [8][9][10][11][12][13][14][15][16][17]. OCT allows acquiring three-dimensional (3D) volumes of the ONH with µm-scale resolution, and with sufficient signal penetration to visualize the lamina cribrosa region within the ONH.…”
Section: Introductionmentioning
confidence: 99%